Implementing a small media intervention to increase colorectal cancer screening in primary care clinics. Issue 4 (1st August 2018) - Melvin, Cathy L; Vines, Anissa I; Deal, Allison M; Pierce, Holly O; Carpenter, William R; Godley, Paul A
Abstract : Patients at average risk for colorectal cancer and not up-to-date on colorectal cancer screening were willing to use a home-based stool test but patients receiving a small media intervention were not more likely to return their test than patients not receiving a small media intervention. Abstract: Colorectal cancer (CRC) is one of the most common cancers in the USA. In 2017, an estimated 135, 420 people were diagnosed with CRC and 50, 260 people died from CRC. Several screening modalities are recommended by the United States Preventive Services Task Force (USPSTF), including annual stool tests that are usually completed at home and under-used compared with colonoscopy despite stated patient preferences for an alternative to colonoscopy. The Community Preventive Services Task Force recommends use of small media interventions (SMIs) to increase CRC screening and calls for a greater understanding of its independent impact on screening participation. This study tested whether a SMI increased the likelihood of participant return of a USPSTF recommended Fecal Immunochemical Test (FIT). In total, 804 individuals participated in a two-group, prospective randomized controlled trial. Descriptive statistics with chi-square tests compared differences in participant characteristics and return rates. Multivariable log-binomial modeling estimated combined effects of patient characteristics with FIT return rates. No differences in return rates were observed overall or by participant characteristics other than the year of enrollment. A multivariable model controlling for all covariates, found gender, insurance type, and regular place for healthcare to be significantly associated with return rates. Receipt of the SMI did not independently increase overall return rates but it may have improved the ease of completing the FIT by some participants, particularly women, those with insurance, and those with a regular place for healthcare.